RENU building a sustainable, ORCID networked knowledge commons in Uganda – shared best practice with the Wits University Libraries - Matizirofa, Lazarus Gallant (University of the Witwatersrand, Johannesburg, 2025)
Abstract not available
This presentation was presented to RENU conference, at Africana Hotel, Kampala, Uganda, on the 09 May 2025.
Keywords: RENU; ORCID; Uganda; Wits University Libraries; Wits Open Access Policies; South Africa Open Access Policies; Open Science; Open Innovation; Research Visibility and Impact; SDG-4: Quality education